Fascinating role of nanosilica in mitigating drought and nutrient stress – A review - Bekkam Rakesh; Chitdeshwari T; Mohanapriya G (Plant Stress)
Drought stress is a major global challenge that severely impacts plant growth, photosynthesis and nutrient uptake, leading to significant yield losses. This necessitates the need for developing new agricultural technologies and one such advancement is nanotechnology. Recently, nanosilica has gained importance due to its significant role in mitigating drought and nutrient stress. The foliar/soil application and seed priming with nanosilica has shown to have positive impacts on plants under drought and nutrient stress by modulating morphological, physiological and biochemical parameters. This review aims to explore the impact of nanosilica in enhancing drought and nutrient stress tolerance in plants by demonstrating its beneficial effects on growth, gas exchange attributes, plant water status, membrane stability, antioxidant activity and silicon mediated uptake of nutrients. Further it also provides an overview of recent developments in nanosilica nutrition of crops and suggests future research directions to understand the role of nanosilica in alleviating drought and nutrient stress.